(3EjVGM eGdGjSY GdeMOK Lgdgs - (3CHh MaU YeQ Hf YHO GdeLjO Hf YeQ GdbQTis
(3ChdgG (B:s
(3CNHQfG Gdabjg bGd GdMeO ddg GdPi habfG dJhMjOg CeG HYO aEfi deG QCjJ JejR GdUMjM ef MOjK QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3Ch MSfg ef ML hYeQg hGQRbfG eG QRbJge ef GdNjQ hGdSYGOg hCeJfG Ydi GdESdGe hGdJhMjO hGdSfI hGdLeGYI hGMTQfG eY GdeJbjf hGdUOjbjf hGdTgOGA hGdUGdMjf ai OGQ GdcQGeg hBNQ OYhGge Cf GdMeO ddg QH GdYGdejf hUdi Gddg Ydi eMeO hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(265 d) s
Keywords: (3GdeLGejYs